Conventional Blending Chitosan Lignin Nanocomposites Hydrogel (CsLNPs) for food coating application - Ahmad Tarmizi, Amelia Shanaz; Othman, Muhammad Bisyrul Hafi; Abdullah Sani, Muhamad Shirwan; Rafiae, Nur Najmina; Rostan, Nur Raihan; Mohamad Ibrahim, Mohamad Nasir (International Institute for Halal Research and Training (INHART) International Islamic University Malaysia, 2025)
Despite the importance of bio-based materials for food coatings, studies on how LNPs enhance thermal stability, swelling behaviour, and barrier properties remain limited, creating a gap in sustainable food preservation solutions. This work successfully prepared the lignin chitosan nanocomposites hydrogel (CsLNPs) via a conventional, cost-effective blending method. The incorporation of LNPs into Cs hydrogels was confirmed via FTIR, showing interactions between LNPs’ -OH groups and Cs’ -NH2 groups, with peak shifts at 3400–3200 cm⁻¹. Thermal analysis revealed decomposition temperatures (Tmax) of 285–290°C, with T10% >170°C and >24% residue at 800°C. Glass transition temperatures (Tg) ranged from 143–154°C. LNPs initially improved thermal stability, although higher loading caused agglomeration, reducing performance. LNPs-Cs hydrogels displayed insolubility in non-polar solvents due to their inherent structure, while increasing lignin loading (5–20%) enhanced water absorption and swelling, slowing fruit rotting. This demonstrated improved moisture and oxygen barrier properties. The findings highlight CsLNPs as a sustainable, effective food coating, reducing waste, promoting eco-friendly packaging, and advancing bio-based solutions for food technology.